RANCANG BANGUN SISTEM INFORMASI PEMBELIAN TUNAI PADA APOTEK MEDIKA PRATAMA DENGAN METODOLOGI BERORIENTASI OBYEK - Ita Novita; Agus Waluyo (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2012)
Nowadays science and technology continues evolve follows the era development. Correspondingly, the need for accurate and fast information is also increasingly felt in all areas. Primary Medical Pharmacies is a company engaged in the sale of medicines and health supplements. The rapid development of business sales transactions which resulted in increasingly increased, so the impact on the supply of drugs should always be available to consumers. For that there needs to be a drug purchase control system is reliable. The purpose of this research is to design a drug purchasing system and apply it in the form of information systems. This study uses UML modeling techniques as one system. Implementation of this study using Microsoft Visual Studio 2005 with the database used is Microsoft Access 2000. The results of the research is the design of information systems that can help the cash purchase transaction in Primary Medical Pharmacy so that later transactions become more effective and efficient which can encourage and enhance the progress of pharmacy. Keywords: Pembelian Tunai, Information System, UML (Unified Modelling Language)